Blue Jacket : warrior of the Shawnees - Sugden, John, 1947 January 27- (American Indian lives., 2000)
Blue Jacket (ca. 1743-ca. 1808), or Wawayapiersenwaw, was the galvanizing force behind an intertribal confederacy of unparalleled scope that fought a long and bloody war against white encroachments into the Shawnees' homeland in the Ohio River Valley. Blue Jacket was an astute strategist and diplomat who, though courted by American and British leaders, remained a staunch defender of the Shawnees' independence and territory. In this arresting and controversial account, John Sugden depicts the most influential Native American leader of his time.